Trajectories in Body Height, Body Weight, BMI, and Nutrition Status From 1979 to 1987: A Measurement-Based Analysis of 15,717 Male Adolescents From the Capital City of Montenegro - Popovic, Stevo; Masanovic, Bojan; Martinovic, Srdja; Bjelica, Dusko; Gardasevic, Jovan (Frontiers in Public Health, 2020)
Introduction and Objective: This study aimed to consolidate body height and body weight, as well as the body mass index and nutrition status data of the entire male population of adolescents from Podgorica, the capital of Montenegro, in order to estimate their trajectories from 1979 to 1987. Methods: The sample includes 15,717 male adolescents divided into nine groups according to their year of birth. The sample of variables includes body height, body weight, and body mass index, as well as nutrition status, which was presented based on BMI standardized categories (underweight, normal weight, pre-obese, obese). The descriptive statistics were expressed as a mean and standard deviation for each variable. Results and Discussion: This study did not observe significant differences in the body proportions and nutritional status of the measured subjects during the observed period. Conclusions: The novelty and the original contribution of this study is reflected in the fact that descriptive data from the second half of the 20th century have been published, which can significantly help to follow the secular trend of one of the tallest nations in the world from the beginning of the 20th century – Montenegro – which has specific body proportions.